The Application of the European Union Taxonomy to Romania’s Largest Energy Firms: Empirical Evidence - Ningshan HAO; Voicu D. DRAGOMIR (Communications of International Proceedings, 2025)
The aim of this paper is to examine the reporting of the contribution of Romania major energy companies listed on the Bucharest Stock Exchange to the European Union (EU) Taxonomy for Sustainable Activities. The EU Taxonomy, set out in Regulation 2020/852, is the EU framework for a classification system for economic activities that can be considered environmentally sustainable and aims to enhance transparency and help to steer investment towards activities contributing to climate and environmental objectives. This regulation has been widely adopted throughout the European Union, yet empirical evidence is scarce regarding how firms operating in Eastern European markets, especially in the energy sector, are reacting to these disclosure requirements. While studies have focused on implementation, researchers have mostly targeted Western Europe, with limited literature on countries such as Romania. In this respect, the research performs a qualitative content analysis of the 2024 sustainability and annual reports of five important Romanian energy companies: OMV Petrom, Hidroelectrica, Nuclearelectrica, Transgaz and Electrica. The evaluation examines the coverage and detail of disclosures related to taxonomy-aligned turnover, capital and operating expenditures, and compliance with the Do No Significant Harm (DNSH) principle and minimum social safeguards. The findings indicate that, while some companies are aware of the taxonomy framework, there remains a lack of consistent and comprehensive reporting practices to demonstrate how their operations align with it. The findings reveal a requirement for improved regulatory guidance and institutional support to enhance the quality and comparability of sustainability disclosures at the EU level.
Keywords: European Union; Taxonomy Regulation; energy sector; sustainable business model; Romania.